Patterns of antenatal care services utilization in rural Amroha, Uttar Pradesh: a community based cross sectional study - Watode, Bhaskar K.; Srivastava, Anurag; Kumar, Rajeev (International Journal Of Community Medicine And Public Health, 2019)
Background: Antenatal care (ANC) services are considered to be the crucial element in the primary health care delivery system of a country. World Health Organization (WHO) estimates suggested that almost all of the maternal deaths (99%) and child deaths (98%) occurred in developing countries. These maternal deaths could have been prevented if the pregnant women or adolescent girls had been able to access quality antenatal care. The objectives of the present study were conducted in rural parts of district Amroha, Uttar Pradesh for assessing the patterns of utilization of the ANC services and to ascertain the factors influencing utilization of ANC services. Methods: The present study was a cross sectional in nature. Recently delivered women were selected as study subject. A multi-stage stratified sampling design with random approaches had been used. Total 360 subjects included in the study. Results: Respondents age, education, occupation, socio economic status, family type and family size were the factors that influenced the utilization of the ANC services. With 100% ANC registration, sub centre was the most preferred place for registration. 76.9% of woman received more than 3 ANC visits. 315 (87.5%) and (71.9%) respondents received 2 doses to TT vaccine and more than 100 IFA tablets respectively. Conclusions: Utilization of ANC services are on rise in rural parts of Amroha, Uttar Pradesh. Still significant proportions of women are doesn’t return to health facility after the ANC registration. Intensification of efforts is needed to cater this left out group through improving community awareness and motivation.